2018
DOI: 10.1016/j.apsusc.2017.11.251
|View full text |Cite
|
Sign up to set email alerts
|

Pressure resistance of copper benzene-1,3,5-tricarboxylate – carbon aerogel composites

Abstract: The protective effect of a resorcinolformaldehyde based carbon aerogel (CA) support was compared in two different forms of the hybrid made of copper benzene-1,3,5-tricarboxilate (HKUST-1) and CA. HKUST-1:CA with identical mass ratio (1:1). HKUST-1+CA is a physical mixture while in HKUST-1@CA the metal organic framework (MOF) crystals were grown on CA under solvothermal conditions. The effect of water vapour and the external pressure (25 -200 bar) was investigated. TG/DTG data show that the prehistory of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The rodlike appearance of the emerging particle was typical for phase I CuTCNQ. [30] The morphology of the CuTCNQ particles was furtherly investigated, after 3 hours of intense ultrasonic treatment in ethanol. The CuTCNQ particles were shaken off from the octahedron, and scatterd spherical and rod-like particles were observed, distinct from the CuBTC octahedron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rodlike appearance of the emerging particle was typical for phase I CuTCNQ. [30] The morphology of the CuTCNQ particles was furtherly investigated, after 3 hours of intense ultrasonic treatment in ethanol. The CuTCNQ particles were shaken off from the octahedron, and scatterd spherical and rod-like particles were observed, distinct from the CuBTC octahedron.…”
Section: Resultsmentioning
confidence: 99%
“…As Table 2 shows, the electronic conductivity of CuBTC was merely 3.84 × 10 À 9 S cm À 1 , agreeing with the insulated property and reported value of CuBTC. [30] The conductivity of composite material CuTCNQ@CuBTC (8 h, 60°C) was improved to 2.79 × 10 À 8 S cm À 1 , by one order of magnitude, owing to the contribution of conductive CuTCNQ shell. With prolonged reaction time, the CuTCNQ shell grew thicker, and therefore the conductivity of core-shell CuTCNQ@CuBTC (24 h, 60°C) increased to 2.94 × 10 À 7 S cm À 1 , by two orders of magnitude.…”
Section: The Property Of Cutcnq@cubtcmentioning
confidence: 97%
“…Sample HA-2 presented the highest CH 4 adsorption capacity of 16.8 mg g −1 at 298 K and 1 bar (Figure 6). Andrea et al synthesized carbon aerogels featuring CH 4 adsorption capacities in the 9.4–23.9 mg g −1 range, which indicated that G/GAs were good adsorbents for CH 4 [31]. However, the adsorption capacity of HA-2 was lower than that of HA-4 at pressures smaller than 0.9 bar, mainly due to the narrow mesoporous structure of the HA-2 sample.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon aerogels have been recognized as potential adsorbents for VOC removal due to their superior features , . For example, Francisco et al prepared a carbon aerogel with gallic acid, resorcinol, and formaldehyde, which was further activated by CO 2 .…”
Section: Applications Based On Adsorption Performancementioning
confidence: 99%